3-x-2(x-3)=3

Simple and best practice solution for 3-x-2(x-3)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-x-2(x-3)=3 equation:


Simplifying
3 + -1x + -2(x + -3) = 3

Reorder the terms:
3 + -1x + -2(-3 + x) = 3
3 + -1x + (-3 * -2 + x * -2) = 3
3 + -1x + (6 + -2x) = 3

Reorder the terms:
3 + 6 + -1x + -2x = 3

Combine like terms: 3 + 6 = 9
9 + -1x + -2x = 3

Combine like terms: -1x + -2x = -3x
9 + -3x = 3

Solving
9 + -3x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + -3x = 3 + -9

Combine like terms: 9 + -9 = 0
0 + -3x = 3 + -9
-3x = 3 + -9

Combine like terms: 3 + -9 = -6
-3x = -6

Divide each side by '-3'.
x = 2

Simplifying
x = 2

See similar equations:

| 0.2x+3=1.5x-12 | | -9(y+7)=45 | | X=-20+2x | | 5(6x-8)= | | 3z/7-6=1 | | -4r-2=7r+9 | | I^3-12I-4=0 | | I^3-2400I-800=0 | | s*6-28=134 | | 10=7a-18 | | -2b+3=4b-5 | | 9t^2-10t^2= | | 2x-20=10-3 | | 4=5+y | | 4x^2-12=-7 | | -y=y+18 | | 3y+12=y+18 | | 7.76=12.76 | | 72+x+2=180 | | x*3+y*3-6xy+8=0 | | 9(a+5)=2(a+1.5) | | 6x^2-6=x | | -5(0.2x+1.4)=20 | | 2x+x+(2x-5)=40 | | X-8+2x=25 | | 3x+x+(2x-5)=40 | | 9t=-21 | | x+5*x+5=36 | | -7t=1 | | y=15x^8-2x^3+6x+7 | | -7(x+1)=5(1-x) | | y=1/2sinx |

Equations solver categories